Strategy-driven leadership : the playbook for developing your next generation of leaders - Couch, Michael A.; Citrin, Richard (New York : Productivity Press, 2019)
It's estimated that U.S. companies spend over $14 billion annually on leadership development --Match that number to the abundant and growing research that finds most leadership development to be ineffective, and the conclusion is a phenomenal amount of waste. The remedy for this situation is to have business strategy drive leadership development instead of creating programs that match a one-size-fits-all approach to leadership. This book's approach, called Strategy-Driven Leadership Development (SDLD), puts business strategy first. It maintains an emphasis on building leadership programs around what it will take to make the business successful as opposed to implementing a program in the hopes that it will benefit the strategy. The result is a differentiated and targeted approach called Intentional Leadership Development, which provides the structure for transforming how leadership development is undertaken. At the heart of this book, however, is the explanation of how small, incremental changes in action and perspective create meaningful changes in the way leadership is developed. The focus is on the leadership behaviors associated with success for any company. Some companies may need leaders with better financial acumen while others may require better teamwork for success. These skills are learnable and when the energy of an organization is behind it, then leadership development can be transformational. The authors method "retools" prior leadership efforts - the emphasis is not on previous failures and restarting with new programs. There are many effective ideas and actions that are currently embedded in leadership programs, but they miss the critical element of tying their efforts to the business strategy. Strategy-Driven Leadership changes the way organizations think about and drive their leadership talent initiatives among their current and upcoming leaders. The book is filled with research, science-based information, case studies, and practical hands-on tools on why and how this Strategy-Driven Leadership Development model will transform company leadership approaches.
OCLC-licensed vendor bibliographic record.
Keywords: Leadership; Success in business; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Workplace Culture; BUSINESS & ECONOMICS / Production & Operations Management